The role of tax law in the national economy - Maulana, Ayang Fristia; Febriyanti, Afi Nurul; Hidayah, Jihan; Azzahra, Siti Alivia; Darly, Doddy (Journal of Law Science, 2024)
The purpose of our research is to discuss "What is the Role of Tax Law in the National Economy", because tax law plays an important role in regulating the country's economic system. The contribution of tax law to national economic stability and growth is the subject of this research. This study focuses on the impact of tax law on investment, consumption, and income distribution by analyzing the tax law framework in the context of fiscal policy. In addition, this study discusses the role of tax law in influencing taxpayer behavior, tax compliance, and government efforts to manage tax revenue to achieve economic development goals. To promote inclusive and sustainable economic growth, this research emphasizes the importance of clear, transparent, and equitable tax laws. Therefore, policymakers can gain useful knowledge about the function of tax law in the context of the national economy